6’-Fluoro[4.3.0]bicyclo nucleic acid: synthesis, biophysical properties and molecular dynamics simulations - Frei, Sibylle; Istrate, Andrei; Leumann, Christian J. (Beilstein Journal of Organic Chemistry, 2018)
Here we report on the synthesis, biophysical properties and molecular modeling of oligonucleotides containing unsaturated 6’-fluoro[4.3.0]bicyclo nucleotides (6’F-bc4,3-DNA). Two 6’F-bc4,3 phosphoramidite building blocks (T and C) were synthesized starting from a previously described [3.3.0]bicyclic sugar. The conversion of this sugar to a gem-difluorinated tricyclic intermediate via difluorocarbene addition followed either by a NIS-mediated or Vorbrüggen nucleosidation yielded in both cases the β-tricyclic nucleoside as major anomer. Subsequent desilylation and cyclopropane ring opening of these tricyclic intermediates afforded the unsaturated 6’F-bc4,3 nucleosides. The successful incorporation of the corresponding phosphoramidite building blocks into oligonucleotides was achieved with tert-butyl hydroperoxide as oxidation agent. Thermal melting experiments of the modified duplexes disclosed a destabilizing effect versus DNA and RNA complements, but with a lesser degree of destabilization versus complementary DNA (ΔTm/mod = −1.5 to −3.7 °C). Molecular dynamics simulation on the nucleoside and oligonucleotide level revealed the preference of the C1’-exo/C2’-endo alignment of the furanose ring. Moreover, the simulation of duplexes with complementary RNA disclosed a DNA/RNA-type duplex structure suggesting that this modification might be a substrate for RNase H.
Keywords: DNA/RNA affinity; fluorinated cyclopropanes; fluorinated nucleic acids; molecular dynamics simulations; sugar modified nucleosides

(untitled) - Stein, C. A.; Castanotto, D. (Mol. Ther., 2017)

(untitled) - Rinaldi, C.; Wood, M. J. A. (Nat. Rev. Neurol., 2018)

(untitled) - Havens, M. A.; Hastings, M. L. (Nucleic Acids Res., 2016)

(untitled) - Shen, X.; Corey, D. R. (Nucleic Acids Res., 2018)

(untitled) - Bennett, C. F.; Swayze, E. E. (Annu. Rev. Pharmacol. Toxicol., 2010)

(untitled) - Kole, R.; Krainer, A. R.; Altman, S. (Nat. Rev. Drug Discovery, 2012)

(untitled) - Spitali, P.; Aartsma-Rus, A. (Cell, 2012)

(untitled) - Cerritelli, S. M.; Crouch, R. J. (FEBS J., 2009)

(untitled) - Lima, W. F.; Nichols, J. G.; Wu, H.; Prakash, T. P.; Migawa, M. T.; Wyrzykiewicz, T. K.; Bhat, B.; Crooke, S. T. (J. Biol. Chem., 2004)

(untitled) - Stanton, R.; Sciabola, S.; Salatto, C.; Weng, Y.; Moshinsky, D.; Little, J.; Walters, E.; Kreeger, J.; DiMattia, D.; Chen, T.; Clark, T.; Liu, M.; et al. (Nucleic Acid Ther., 2012)

(untitled) - Juliano, R.; Bauman, J.; Kang, H.; Ming, X. (Mol. Pharmaceutics, 2009)

(untitled) - Herdewijn, P. (Biochim. Biophys. Acta, Gene Struct. Expression, 1999)

(untitled) - Obika, S.; Nanbu, D.; Hari, Y.; Morio, K.-i.; In, Y.; Ishida, T.; Imanishi, T. (Tetrahedron Lett., 1997)

(untitled) - Koshkin, A. A.; Singh, S. K.; Nielsen, P.; Rajwanshi, V. K.; Kumar, R.; Meldgaard, M.; Olsen, C. E.; Wengel, J. (Tetrahedron, 1998)

(untitled) - Itoh, M.; Nakaura, M.; Imanishi, T.; Obika, S. (Nucleic Acid Ther., 2014)

(untitled) - Hendrix, C.; Rosemeyer, H.; Verheggen, I.; Van Aerschot, A.; Seela, F.; Herdewijn, P. (Chem. – Eur. J., 1997)

(untitled) - Herdewijn, P. (Chem. Biodiversity, 2010)

(untitled) - Wang, J.; Verbeure, B.; Luyten, I.; Lescrinier, E.; Froeyen, M.; Hendrix, C.; Rosemeyer, H.; Seela, F.; Van Aerschot, A.; Herdewijn, P. (J. Am. Chem. Soc., 2000)

(untitled) - Nauwelaerts, K.; Fisher, M.; Froeyen, M.; Lescrinier, E.; Van Aerschot, A.; Xu, D.; DeLong, R.; Kang, H.; Juliano, R. L.; Herdewijn, P. (J. Am. Chem. Soc., 2007)

(untitled) - Steffans, R.; Leumann, C. (Helv. Chim. Acta, 1997)

(untitled) - Steffens, R.; Leumann, C. J. (J. Am. Chem. Soc., 1999)

(untitled) - Goyenvalle, A.; Griffith, G.; Babbs, A.; El Andaloussi, S.; Ezzat, K.; Avril, A.; Dugovic, B.; Chaussenot, R.; Ferry, A.; Voit, T.; Amthor, H.; Bühr, C.; et al. (Nat. Med., 2015)

(untitled) - Stauffiger, A.; Leumann, C. J. (Eur. J. Org. Chem., 2009)

(untitled) - Biffinger, J. C.; Kim, H. W.; DiMagno, S. G. (ChemBioChem, 2004)

(untitled) - Böhm, H.-J.; Banner, D.; Bendels, S.; Kansy, M.; Kuhn, B.; Müller, K.; Obst-Sander, U.; Stahl, M. (ChemBioChem, 2004)

(untitled) - Rigo, F.; Hua, Y.; Chun, S. J.; Prakash, T. P.; Krainer, A. R.; Bennett, C. F. (Nat. Chem. Biol., 2012)

(untitled) - Swallow, S. (Prog. Med. Chem., 2015)

(untitled) - Gillis, E. P.; Eastman, K. J.; Hill, M. D.; Donnelly, D. J.; Meanwell, N. A. (J. Med. Chem., 2015)

(untitled) - Guo, F.; Li, Q.; Zhou, C. (Org. Biomol. Chem., 2017)

(untitled) - Kawasaki, A. M.; Casper, M. D.; Freier, S. M.; Lesnik, E. A.; Zounes, M. C.; Cummins, L. L.; Gonzalez, C.; Cook, P. D. (J. Med. Chem., 1993)

(untitled) - Patra, A.; Paolillo, M.; Charisse, K.; Manoharan, M.; Rozners, E.; Egli, M. (Angew. Chem., 2012)
Angew. Chem., Int. Ed. 2012, 51, 11863–11866. doi:10.1002/anie.201204946

(untitled) - Wilds, C. J.; Damha, M. J. (Nucleic Acids Res., 2000)

(untitled) - Kalota, A.; Karabon, L.; Swider, C. R.; Viazovkina, E.; Elzagheid, M.; Damha, M. J.; Gewirtz, A. M. (Nucleic Acids Res., 2006)

(untitled) - Souleimanian, N.; Deleavey, G. F.; Soifer, H.; Wang, S.; Tiemann, K.; Damha, M. J.; Stein, C. A. (Mol. Ther. - Nucleic Acids, 2012)

(untitled) - Egli, M.; Pallan, P. S.; Allerson, C. R.; Prakash, T. P.; Berdeja, A.; Yu, J.; Lee, S.; Watt, A.; Gaus, H.; Bhat, B.; Swayze, E. E.; Seth, P. P. (J. Am. Chem. Soc., 2011)

(untitled) - Seth, P. P.; Yu, J.; Jazayeri, A.; Pallan, P. S.; Allerson, C. R.; Østergaard, M. E.; Liu, F.; Herdewijn, P.; Egli, M.; Swayze, E. E. (J. Org. Chem., 2012)

(untitled) - Seth, P. P.; Pallan, P. S.; Swayze, E. E.; Egli, M. (ChemBioChem, 2013)

(untitled) - Jung, M. E.; Dwight, T. A.; Vigant, F.; Østergaard, M. E.; Swayze, E. E.; Seth, P. P. (Angew. Chem., 2014)
Angew. Chem., Int. Ed. 2014, 53, 9893–9897. doi:10.1002/anie.201405283

(untitled) - Østergaard, M. E.; Dwight, T.; Berdeja, A.; Swayze, E. E.; Jung, M. E.; Seth, P. P. (J. Org. Chem., 2014)

(untitled) - Martínez-Montero, S.; Deleavey, G. F.; Martín-Pintado, N.; Fakhoury, J. F.; González, C.; Damha, M. J. (ACS Chem. Biol., 2015)

(untitled) - Martínez-Montero, S.; Deleavey, G. F.; Dierker-Viik, A.; Lindovska, P.; Ilina, T.; Portella, G.; Orozco, M.; Parniak, M. A.; González, C.; Damha, M. J. (J. Org. Chem., 2015)

(untitled) - Dugovic, B.; Leumann, C. J. (J. Org. Chem., 2014)

(untitled) - Medvecky, M.; Istrate, A.; Leumann, C. J. (J. Org. Chem., 2015)

(untitled) - Istrate, A.; Katolik, A.; Istrate, A.; Leumann, C. J. (Chem. – Eur. J., 2017)

(untitled) - Istrate, A.; Medvecky, M.; Leumann, C. J. (Org. Lett., 2015)

(untitled) - Fedorov, O. V.; Kosobokov, M. D.; Levin, V. V.; Struchkova, M. I.; Dilman, A. D. (J. Org. Chem., 2015)

(untitled) - Kageshima, Y.; Suzuki, C.; Oshiro, K.; Amii, H. (Synlett, 2015)

(untitled) - Wu, S.-H.; Yu, Q. (Acta Chim. Sin. (Engl. Ed.), 1989)

(untitled) - Song, X.; Chang, J.; Zhu, D.; Li, J.; Xu, C.; Liu, Q.; Wang, M. (Org. Lett., 2015)

(untitled) - Luisier, S.; Leumann, C. J. (Heterocycles, 2010)

Screening the structural and functional properties of bicyclo-DNA - Luisier, S. (University of Bern, 2008)

(untitled) - Wang, F.; Luo, T.; Hu, J.; Wang, Y.; Krishnan, H. S.; Jog, P. V.; Ganesh, S. K.; Prakash, G. K. S.; Olah, G. A. (Angew. Chem., 2011)
Angew. Chem., Int. Ed. 2011, 50, 7153–7157. doi:10.1002/anie.201101691

(untitled) - Luisier, S.; Silhar, P.; Leumann, C. J. (Nucleic Acids Symp. Ser., 2008)

(untitled) - Lietard, J.; Leumann, C. J. (J. Org. Chem., 2012)

(untitled) - Luche, J.-L. (J. Am. Chem. Soc., 1978)

(untitled) - Luche, J.-L.; Rodriguez-Hahn, L.; Crabbé, P. (J. Chem. Soc., Chem. Commun., 1978)

(untitled) - Vorbrüggen, H.; Krolikiewicz, K.; Bennua, B. (Chem. Ber., 1981)

(untitled) - Tarköy, M.; Bolli, M.; Leumann, C. (Helv. Chim. Acta, 1994)

(untitled) - Sekiguchi, M.; Obika, S.; Harada, Y.; Osaki, T.; Somjing, R.; Mitsuoka, Y.; Shibata, N.; Masaki, M.; Imanishi, T. (J. Org. Chem., 2006)

(untitled) - Scheuer-Larsen, C.; Dahl, B. M.; Wengel, J.; Dahl, O. (Tetrahedron Lett., 1998)

(untitled) - Dugovic, B.; Wagner, M.; Leumann, C. J. (Beilstein J. Org. Chem., 2014)

(untitled) - Evéquoz, D.; Leumann, C. J. (Chem. – Eur. J., 2017)

(untitled) - Petersheim, M.; Turner, D. H. (Biochemistry, 1983)

(untitled) - Bolli, M.; Trafelet, H. U.; Leumann, C. J. (Nucleic Acids Res., 1996)

Gaussian 09, Revision A.02 (Gaussian, Inc., 2009)

(untitled) - Dupradeau, F.-Y.; Pigache, A.; Zaffran, T.; Savineau, C.; Lelong, R.; Grivel, N.; Lelong, D.; Rosanski, W.; Cieplak, P. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Cornell, W. D.; Cieplak, P.; Bayly, C. I.; Gould, I. R.; Merz, K. M., Jr; Ferguson, D. M.; Spellmeyer, D. C.; Fox, T.; Caldwell, J. W.; Kollman, P. A. (J. Am. Chem. Soc., 1995)

(untitled) - Van Der Spoel, D.; Lindahl, E.; Hess, B.; Groenhof, G.; Mark, A. E.; Berendsen, H. J. C. (J. Comput. Chem., 2005)

(untitled) - Olson, W. K.; Bansal, M.; Burley, S. K.; Dickerson, R. E.; Gerstein, M.; Harvey, S. C.; Heinemann, U.; Lu, X.-J.; Neidle, S.; Shakked, Z.; Sklenar, H.; Suzuki, M.; et al. (J. Mol. Biol., 2001)

(untitled) - El Hassan, M. A.; Calladine, C. R. (J. Mol. Biol., 1998)

(untitled) - Nowotny, M.; Gaidamakov, S. A.; Ghirlando, R.; Cerritelli, S. M.; Crouch, R. J.; Yang, W. (Mol. Cell, 2007)